CULTURAL STRUGGLE DURING TIME OF CRISIS REFLECTED IN RON HOWARD HILLBILLY ELEGY (2020): A FEMINIST APPROACH - Marwa Salsabila (Jurusan Sastra Indonesia, 2022)
This paper examines the Cultural struggle during the time of crisis movie “Hillbilly Elegy”. The purpose of this paper is to identify what is the indicators of cultural struggle during the time of crisis reflected in “Hillbilly Elegy” and to describe the depiction of cultural struggle during the time of crisis reflected in “Hillbilly Elegy” The research uses qualitative as a method in this review.